Inventor mobility, knowledge diffusion, and growth - Yasutaka Koike-Mori; Toshitaka Maruyama; Koki Okumura (Osaka University, Institute of Social and Economic Research (ISER), 2024)
This paper develops an endogenous growth model that incorporates a frictional inventor market and examines the allocation of inventors across firms, knowledge diffusion, and its impact on growth. In our model, inventors play dual roles: they engage in in-house R&D and transfer knowledge from previous employers to new ones when changing jobs. Using an administrative panel dataset on German inventors matched to their employing establishments and patents, we find that, relative to general workers, inventors are more likely to transition to less productive establishments and suffer a higher wage growth via the transition. We also find that the knowledge base of establishments measured by patents grows faster when a significant proportion of their inventors originate from establishments possessing a larger knowledge base. We then calibrate the model to reflect these empirical findings and examine the effects of innovation policy. While subsidies to frontier firms discourage knowledge diffusion from these firms to technologically lagging firms, these subsidies also encourage innovation within frontier firms. The former negative effect dominates in the short term, but the latter positive effect dominates in the long run.
Keywords: 330; Invention; Highly skilled labor; Labor mobility; Knowledge transfer; Economic growth; Endogenous growth model; Germany; Erfindung; Hochqualifizierte Arbeitskräfte; Arbeitsmobilität; Wissenstransfer; Wirtschaftswachstum; Endogenes Wachstumsmodell; Deutschland